Blockchain-based solutions for accessibility in smart cities - Abhishek, Kumar; Chakraborty, Chinmay 1984- (Advances in civil and industrial engineering (ACIE) book series, 2024)
In the evolving landscape of smart cities, the integration of technology and real-time data management presents a dual-edged challenge and opportunity for urban accessibility. The web of devices, from smartphones and connected cars to homes and citizens, forms the backbone of a smart city's infrastructure. As cities strive to become technologically enhanced hubs, the need for seamless accessibility becomes paramount. However, this ambitious transformation encounters hurdles such as traffic congestion, inefficient energy distribution, and concerns about air quality. Enter Blockchain-Based Solutions for Accessibility in Smart Cities, a groundbreaking exploration that addresses the issues hindering the optimal realization of smart city accessibility. This book delves into the emergence of blockchain technologies within smart city infrastructures and offers a compelling narrative on how blockchain-based solutions can be the catalyst for overcoming these challenges. This innovative book is crafted with a specific audience in mind - researchers, faculty, and students committed to shaping a secure ecosystem for smart city infrastructure. By merging concepts of security, smart city infrastructure, and blockchain, this multidisciplinary approach ensures that readers gain a nuanced understanding of the challenges at hand. Whether immersed in academia or eager to contribute to the evolution of smart cities, Blockchain-Based Solutions for Accessibility in Smart Cities is a valuable resource that empowers readers to navigate the complexities and unlock the full potential of blockchain in urban accessibility.